From hot to cold - The temperature dependence on rock deformation processes: An introduction. (March 2020) - Gomez-Rivas, Enrique; Butler, Robert W.H.; Healy, David; Alsop, Ian
Abstract: Understanding rock deformation processes in solid Earth materials, from the crystal to the tectonic plate scale, is essential for characterising the evolution of the lithosphere and for predicting how rocks behave in the subsurface. Temperature is a key parameter that determines what rock deformation processes are active and therefore how tectonic structures form. Moreover, it controls the migration of fluids and melt in the Earth's crust that lead to phase transformations and changes in rock rheology. This special issue gathers a collection of research papers following the 21st International Conference on Deformation Mechanisms, Rheology and Tectonics (DRT-2017), which was held in Inverness (Scotland) in April–May 2017, organised by the University of Aberdeen. These contributions provide a significant advance in the study of rock deformation and fluid/melt migration at multiple crustal levels, from deformation bands near the Earth's surface to shear zones in partially molten rocks in the lower crust. In this introductory article, we first provide an overview of how temperature controls deformation mechanisms and processes and then introduce the collection of research papers ordered from those analysing deformation processes occurring at high temperatures to contributions reporting deformation at shallow crustal conditions. Highlights: This special issue provides significant advances in the study of rock deformation. A brief summary of how temperature controls rock deformation processes is presented. The special issue articles are introduced, from deep to shallow crustal studies.